Analyzing The Effects of Compensation, Recognition, Work Environment, and Employee Engagement On Employee Performance: A Case Study of Small-Sized Food and Beverage Company in Jakarta (Cv Payu Rasa Indonesia) - Fariz Muhammad (International Journal of Science and Environment (IJSE), 2026)
Employee performance plays a pivotal role in determining the operational success and competitiveness of a company. At CV Payu Rasa Indonesia, sustaining high employee performance requires understanding the key factors that influence it, including compensation, work environment, recognition, and employee engagement. This study aims to examine the positive and significant effects of these four strategic areas on employee performance. A quantitative explanatory approach was employed, using a survey distributed to 100 employees selected through purposive sampling. The data were collected using a Google Form questionnaire based on a five-point Likert scale. The collected data underwent validity and reliability testing, classical assumption tests, and multiple linear regression analysis. The study is grounded in motivational and organizational behavior theories, which posit that employees’ performance outcomes are shaped by both tangible rewards and psychological engagement factors. The results reveal that compensation, work environment, recognition, and employee engagement each have a positive and significant effect on employee performance, both partially and simultaneously. The regression model yields an R² value of 0.759, indicating that the four variables collectively explain 75.9% of the variation in employee performance. Among these, compensation emerges as the most influential factor. These findings highlight the importance for the company to provide fair and competitive compensation, ensure a conducive work environment, implement structured recognition programs, and strengthen employee engagement to drive sustained performance improvements.